Periodontal response to orthodontic tooth movement in diabetes-induced rats with or without periodontal disease - Ferreira, Camila Lopes [UNESP]; Rocha, Vinicius Clemente da [UNESP]; Silva Ursi, Weber Jose da [UNESP]; De Marco, Andrea Carvalho [UNESP]; Santamaria, Milton; Santamaria, Mauro Pedrine [UNESP]; Neves Jardini, Maria Aparecida [UNESP] (Amer Acad Periodontology, 2018)
Background: Systemic conditions can influence orthodontic tooth movement. This study evaluates histologic periodontal responses to orthodontic tooth movement in diabetes-induced rats with or without periodontal disease. Methods: Forty Wistar rats were divided according their systemic condition (SC) into diabetic (D) and non-diabetic (ND) groups. Each group was subdivided into control (C), orthodontic tooth movement (OM), ligature-induced periodontitis (P) and ligature-induced periodontitis with orthodontic movement (P+OM) groups. Diabetes mellitus (DM) was induced with alloxan monohydrate, and after 30 days, the P group received a cotton ligature around their first lower molar crown. An orthodontic device was placed in OM and P+OM groups for 7 days, and the animals were then euthanized. Results: Differences in OM between D and ND groups were not significant (6.87 +/- 3.55 mm and 6.81 +/- 3.28 mm, respectively), but intragroup analysis revealed statistically significant differences between the P+OM groups for both SCs. Bone loss was greater in the D group (0.16 +/- 0.07 mm(2)) than in the ND group (0.10 +/- 0.03 mm(2)). In intragroup analysis of the D condition, the P+OM group differed statistically from the other groups, while in the ND condition, the P+OM group was different from the C and OM groups. There was a statistically significant difference in bone density between D and ND conditions (18.03 +/- 8.09% and 22.53 +/- 7.72%) in the C, P, and P+OM groups. Conclusion: DM has deleterious effects on bone density and bone loss in the furcation region. These effects are maximized when associated with ligature-induced periodontitis with orthodontic movement.
Keywords: Alloxan diabetes; orthodontic tooth movement; periodontal disease